Strategies and Successful Practices of Innovation in the Automotive Industry - TOLAMATL-MICHCOL, Jacobo; GALLARDO-GARCÍA, David; VARELA-LOYOLA, José Antonio; MÉNDEZ-MENDOZA, José Nemorio (ECORFAN-Mexico, 2018)
The quality of a product in the Automotive Industry demands that its suppliers comply with the requirements in each of its mobile, rigid or joining components between the elements that make up the function and operation of an automotive device; so in this study the adhesion operation of a mixture of additives, catalysts and solvents for adhesion of microfibers (flock) of automotive parts is analyzed, applying an Experiment Design (DoE) that allows an adhesion response and the final product present an aesthetic and functional sensation to the geometry of the piece. The methodological process consists of the application of the DoE that Montgomery (2005) proposes, the use of basic quality tools including the analysis of the effect of failure in the operational process of adherence of the materials and the support of the software Minitab 17 Statistical. The results obtained when implementing the DoE was a mixture of 1100 ml for the adhesive, 900 ml for the catalyst and 1000 ml for the solvent to obtain a flock adhesion of microfibers of a height of 0.9 mm in a time interval of 50 to 60 seconds.